Dynamic environmental control mechanisms for pneumatic foil constructions - Flor, Jan-Frederik; Wu, Yupeng; Beccarelli, Paolo; Chilton, John (EDP Sciences, 2017)
Membrane and foil structures have become over the last decades an attractive alternative to conventional materials and building systems with increasing implementation in different typologies and scale. The development of transparent, light, flexible and resistant materials like Ethylene Tetrafluoroethylene (ETFE) has triggered a rethinking of the building envelope in the building industry towards lightweight systems. ETFE foil cushions have proven to fulfil the design requirements in terms of structural efficiency and aesthetic values. But the strategies to satisfy increasing demands of energy efficiency and comfort conditions are still under development. The prediction and manipulation of the thermo-optical behaviour of ETFE foil cushion structures currently remain as one of the main challenges for designers and manufacturers. This paper reviews ongoing research regarding the control of the thermo-optical performance of ETFE cushion structures and highlights challenges and possible improvements. An overview of different dynamic and responsive environmental control mechanisms for multilayer foil constructions is provided and the state of the art in building application outlined by the discussion of case studies